Association of Lactate Clearance with Morbidity and Mortality in Neonates with Sepsis and Septic Shock at RECEP Tayyip Erdogan Hospital Muzaffargarh - Mehwish Iqbal, Athar Razzaq, Fiaz Ahmad Malik, Muhammad Ali, Muhammad Imran, Maham Shehzadi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: to determine the association of lactate clearance with morbidity and mortality in neonates with sepsis and septic shock at neonatology department of Recep Tayyip Erdogan Hospital Muzaffargarh. Methods: This prospective cohort study was carried out at department of neonatology of Recep Tayyip Erdogan Hospital Muzaffargarh from January 2021 to June 2021. Term neonates, aged less than 28 days and diagnosed as the cases of sepsis, were included. After taking demographic information, a detailed medical history was obtained, and a complete clinical examination was done. Blood samples were taken from all the patients and sent to the Hospital diagnostic laboratory to evaluate the CBC, liver function test, serum creatinine level, coagulation profile, CRP, blood culture, and serum lactate level. All the data were collected by using structured study proforma, and SPSS version 26 was used for the purpose of data analysis. Results: A total of 56 septic neonates were studied, their mean age was 13.14+7.79 days. Females were 51.8% and males were 48.2%. Blood culture was positive in 75.0% of the cases, and CRP was positive in 98.2% of the cases. Overall average of serum lactate at baseline was 2.67+1.73, at 6 hours was 1.91+0.98 and at 24 hours average of serum lactate was 0.21+0.10. 50% of the cases had AKI, 50.0% had AHI, cardiac failure was in 26.8% of the cases, 30.4% of the cases had need of ventilation, and the mortality rate was 35.7%. Septic neonatal morbidity and mortality were statistically insignificant according to serum lactate at baseline and at 24 hours (p >0.05). Despite the fact that serum lactate at 6 hours was significantly associated with mortality and the need for ventilation (p 0.05), Conclusion: As per the study conclusion, neonatal sepsis and septic shock are highly responsible for neonatal morbidity and mortality. Lactate clearance at six hours was found to be significantly related to neonatal mortality and the need for ventilation. Although lactate clearance at 6 hours is observed to be a predictor of neonatal mortality in neonates with sepsis and septic shock, Keywords: Neonatal sepsis, lactate clearance, morbidity, mortality